Morphometry of seeds of Lachesiodendron viridiflorum (Fabaceae) - Nogueira, Ariane da Silva; Carvalho, Leticia Renata de; Silva, Leonardo Máximo; Silva, Leovandes Soares da; Sales, Nilza de Lima Pereira (Brazilian Journal of Production Engineering, 2023)
Lachesiodendron viridiflorum, popularly known as surucaina, is a native tree species in Brazil that has potential for the recovery of degraded areas, and for the generation of timber and non-timber products. The present study aimed to describe physical characteristics of seeds from two matrices of L. viridiflorum located in the North region of Minas Gerais. Seeds collected in Montes Claros and Nova Porteirinha were evaluated for: biometric characteristics (length, width and thickness), weight of a thousand seeds, number of seeds per kilogram, water content and seed shape. Seeds exhibited little variation in biometric aspects within each batch, especially in relation to thickness. Between batches, statistical difference was observed only for thickness. As for the format, the seeds of both lots were classified as spherical and flattened. Positive and significant correlations that differed between the two lots were found between width and thickness, as well as between width and surface area and seed volume variables. This information contributes to seed technology and obtaining lots for the use of that species.